Aktivitas Antioksidan Serum Gel dari Ekstrak Biji Asam Jawa (Tamarindus indica L) sebagai Penangkal Radikal Bebas dan Pencerah Wajah - Farid Ahmad; Siti Ningrum Ratna Ningsih; Nia Yuniarsih (Jurnal Health Sains, 2022)
Damage to the facial skin will interfere with the health and appearance of humans so that the facial skin needs to be protected and maintained its health. One of the factors causing damage to facial skin is free radicals. Free radicals can be found in a dirty environment, it is necessary to have an alternative route for free radical scavengers, namely Serum gel from Tamarind Seed Extract (Tamarindus Indica L.) The method used in this study is to use Literature Review Article (LRA). The literature mentions that Tamarind Seeds have a very high antioxidant content. Antioxidant testing on Tamarind Seeds uses the DPPH method (2,2-diphenyl-1-picrylhydrazil) with stable results and has gone through guaranteed clinical test parameters.